Conservative Management of Keratocystic Odontogenic Tumors of Jaws - Nurhan Güler; Kemal Şençift; Özge Demirkol (The Scientific World Journal)
Purpose. The aim of this study was to evaluate different surgical treatment methods for keratocystic odontogenic tumors (KCOTs) and the outcome of those treatments over a 9-year period. Patients and Methods. A retrospective review was performed on 43 KCOTs in 39 patients. In radiographic evaluations for diagnosis, follow ups and before and after treatment, panoramic, 3D CT and MR images were used. The three groups of different surgical treatment were (1) enucleation for small unilocular lesions without certainty of histology; (2) enucleation with Carnoy's solution, for small unilocular lesions after previous histological confirmation of KOCT; (3) marsupialization followed by enucleation with Carnoy's solution implemented for large often multilocular KCOTs with intact or destruction of cortical bone without infiltration of neighbouring tissue. Results. 43 KCOT cases were mostly localized in mandible (76.7%), radiologically unilocular (72%), and parakeratocysts (88.4%). Inflammation and satellite cysts (daughter cysts) were detected histopathologically in 14 (32.5%) and 7 (16.3%), respectively. Among the 43 cysts, 20 (46.5%) were associated with the impacted third molar and of 21 (48.8%) was in tooth bearing area, and 5 (11, 6%) located on edentulous areas. It was located mostly in the anterior region of maxilla (90%) and in mandibular molar and ramus (62.8%). The treatments of KCOTs were 18 (41.9%) for group 1, and 10 (23.3%) group 2, and 15 (34.8%) group 3. A statistically significant relationship was found between the radiographic appearance and treatment methods (𝑃=0.00). No recurrence was found on 40.54±23.02 months follow up. Conclusion. We concluded that successful treatment methods were enucleation and Carnoy's solution in small lesions and marsupialization in lesions that have reached a very large size, but because KCOT was observed in second decade mostly, long-term follows up are suggested.